2021
DOI: 10.1038/s42003-021-01902-y
|View full text |Cite
|
Sign up to set email alerts
|

A Vaspin–HSPA1L complex protects proximal tubular cells from organelle stress in diabetic kidney disease

Abstract: Proximal tubular cells (PTCs) are crucial for maintaining renal homeostasis, and tubular injuries contribute to progression of diabetic kidney disease (DKD). However, the roles of visceral adipose tissue-derived serine protease inhibitor (vaspin) in the development of DKD is not known. We found vaspin maintains PTCs through ameliorating ER stress, autophagy impairment, and lysosome dysfunction in DKD. Vaspin−/− obese mice showed enlarged and leaky lysosomes in PTCs associated with increased apoptosis, and thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Vaspin exerts multiple beneficial effects in the context of obesity and especially obesity-related comorbidities, as well as liver and vascular inflammation (reviewed in ( 11 , 12 )). Important tools to study and establish the function of this intriguing serpin were vaspin-knockout and vaspin transgenic mouse models ( 10 , 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Vaspin exerts multiple beneficial effects in the context of obesity and especially obesity-related comorbidities, as well as liver and vascular inflammation (reviewed in ( 11 , 12 )). Important tools to study and establish the function of this intriguing serpin were vaspin-knockout and vaspin transgenic mouse models ( 10 , 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…HSPA1L possesses a highly conserved domain structure crucial for protein stabilization, cell proliferation, and apoptosis, as well as cell signal transduction. 20 HSPA1L forms a complex with lamp2 promotes chaperon‐mediated autophagy (CMA), 43 and induces the translocation of Parkin to the damaged mitochondria via P62 inhibition. Since HSPA1L is an important interacting protein of Parkin, 20 MFG‐E8 regulates mitophagy and could be realized through a novel signal pathway (MFG‐E8‐HSPA1L‐Parkin).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, a study on the mechanism of high doses of vitamin E treatment with DKD had shown that high doses of vitamin E could promote lysosomal function and reduce autophagic stress to delay the progression of DKD ( Zhao Y. et al, 2018 ). In addition to this, in order to investigate the role of the vaspin-HSPA1L (heat shock protein family A member 1 like) complex in the development of DKD, the present study made use of patients with obesity-related nephropathy and DKD as well as high-fat and high-glucose-induced mice as models, and then concluded that the vapsin/HSPA1L-mediated pathway played a role in ER stress, impaire autophagy and lysosomal function ( Nakatsuka et al, 2021 ). In summary, the formation of the autolysosome is another key pathway in the autophagic process and is related to the degradation of intracellular metabolites ( Wu M. et al, 2021 ).…”
Section: Dkd and Autophagymentioning
confidence: 99%